Optimization Of The Use Of Inorganic Waste As A Planting Media For Pachira Aquatica In Pucuksari Village - Febriyanti, Triyana; Putri, Nuriskha Amanda (Jurnal Pengabdian Masyarakat Bangsa, 2024)
Waste is quite a serious problem that impacts the environment and the existence of awareness from the public For handling the problem of waste said. Utilization of waste is one of the ways that can done in public Village Pucuksari. The utilization carried out village The Pucuksari to waste is with recycling repeat waste gallon plastic very use to be a pot for plant pachira. Besides For utilization of waste matter, this aims to introduce plant pachira to the public village Pucuksari. Method research used​ that is qualitative with type descriptive. Study studies fieldwork carried out when the researcher carries out devotion in the village or Studying Work Real (KKN) in the village Pucuksari, District Weleri, Kendal Regency. An object from study This is the public village Pucuksari. Data collection techniques, namely through observation, interviews, and documentation.